2022
DOI: 10.4103/0028-3886.355137
|View full text |Cite
|
Sign up to set email alerts
|

A Dysfunctional Descending Pain Modulation System in Chronic Nonspecific Low Back Pain

Abstract: Pain, a protective mechanism turns into a pathologic response when it becomes chronic.Recent evidences are pointing towards neuroplastic brain changes as the primary factor for the persisting pain in chronic nonspecific low back pain (cLBP). To summarise the previous fMRI studies, a coordinate-based ALE meta-analysis of resting functional brain imaging studies is carried out to identify the clusters activated in the brain in cLBP.Literature survey: 'PubMed', 'Scopus' and 'Sleuth' were searched for studies with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…From the aforementioned findings, it is evident that chronic pain can generate both common and specific structural and functional changes in the brain neural networks, dependent on the pathology that affects the person ( Cauda et al, 2014 ) and denote the complexity of the neural mechanisms underlying chronic pain ( Baliki et al, 2014 ). The results of this review also demonstrated that knee OA pain affects brain areas responsible of the sensory-discriminative, cognitive and affective dimensions of pain ( Hazra et al, 2022 ). Concretely, structural and functional alterations in different somatosensory and motor brain regions, such as the precentral and postcentral gyrys, paracentral gyrus (where the primary somatosensory and motor areas from the lower limb are located), cerebellum, and basal ganglia were found and were related to the perception-motor response of pain ( Fenton, Shih & Zolton, 2015 ; Hazra et al, 2022 ).…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…From the aforementioned findings, it is evident that chronic pain can generate both common and specific structural and functional changes in the brain neural networks, dependent on the pathology that affects the person ( Cauda et al, 2014 ) and denote the complexity of the neural mechanisms underlying chronic pain ( Baliki et al, 2014 ). The results of this review also demonstrated that knee OA pain affects brain areas responsible of the sensory-discriminative, cognitive and affective dimensions of pain ( Hazra et al, 2022 ). Concretely, structural and functional alterations in different somatosensory and motor brain regions, such as the precentral and postcentral gyrys, paracentral gyrus (where the primary somatosensory and motor areas from the lower limb are located), cerebellum, and basal ganglia were found and were related to the perception-motor response of pain ( Fenton, Shih & Zolton, 2015 ; Hazra et al, 2022 ).…”
Section: Discussionmentioning
confidence: 76%
“…The results of this review also demonstrated that knee OA pain affects brain areas responsible of the sensory-discriminative, cognitive and affective dimensions of pain ( Hazra et al, 2022 ). Concretely, structural and functional alterations in different somatosensory and motor brain regions, such as the precentral and postcentral gyrys, paracentral gyrus (where the primary somatosensory and motor areas from the lower limb are located), cerebellum, and basal ganglia were found and were related to the perception-motor response of pain ( Fenton, Shih & Zolton, 2015 ; Hazra et al, 2022 ). Therefore, the frontal cortex also has an important role in the integration of pain sensation, since it is responsible for behaviours related to pain after receiving information from other areas of the brain responsible for processing pain information ( Fenton, Shih & Zolton, 2015 ).…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations